ANALISIS SISTEM AKUNTANSI PENJUALAN DAN PENERIMAAN KAS PADA CV. MJ PERFUME MEDAN - Hartini, Sri Indah; Marviana, Ratna Dina; Zahari, Zahari (Worksheet : Jurnal Akuntansi, 2023)
Observations made at CV. MJ Perfume Medan, there are various problems faced by the company inimplementing the sales accounting system and cash receipts system, so the implementation of the cashreceipts system sales accounting system requires several improvements so that it will be able to produceaccurate information, which will later be useful for company management in decision making. decision.The problem in this research is to analyze the systems and procedures for recording sales and cashreceipts applied by CV. MJ Perfume Medan. The type of research used is descriptive research, namely aresearch conducted by collecting, compiling, analyzing, and designing the existing accounting systemon the CV. MJ Perfume Medan.The results of the study concluded that the CV. MJ Perfume Medan hasrun a cash sales accounting system manually and it is still very simple. The cash sales system is goodenough. Documents used in the credit sales system on CV. MJ Perfume Medan, namely: order receiptrecords, sales invoices, travel documents and delivery of goods. While the accounting records used incredit sales include accounts receivable books, sales journals. In accounting records are still verysimple. Cash receipts accounting system on the CV. MJ Perfume Medan has been running well becausethe information from cash receipts activities can be adjusted to what is needed by the company'smanagement. This is supported by the procedure for recording cash receipts from sales used to recordcash receipts transactions.